Stability of Close Chambers Surrounding Rock in Deep and Comprehensive Control Technology - Weijian Yu; Fangfang Liu (Advances in Civil Engineering)
The purpose of this paper is to solve the problem that deep and close-distance cavern and roadway group were easily affected by the adjacent chamber or roadway excavation disturbance and low stability and significant deformation of surrounding rock occurred. The stability and control technology of surrounding rock in the main shaft and auxiliary shaft system has been analyzed by the adjacent chamber and roadway group of −850 m level in Qujiang Mine, China, as an engineering background. Firstly, the numerical calculation of the excavation chamber was, respectively, carried out in different ways with the propagation theory of the excavation disturbance wave. The results show that the interaction of adjacent chamber excavation was more intense. When excavated at the same time, there is a large increase in the movement of the sides and the roof-floor of the chamber and roadway. Then, the mechanism of interaction between low-high stress and excavation disturbance was considered, the corresponding control principles were provided, and a set of critical technologies and equipment were designed according to the deformation characteristics of the large deformation soft surrounding rock. Finally, the comprehensive control method was put forward with the water pump house as an example, that is, anchor, metal net, grouting, combined anchor cable and large-diameter anchor cable. And the related support parameters were determined by the internal damage of the surrounding rock chamber. The numerical simulation results show that the surrounding rock deformation of the chamber and roadway reduced with the revised support program, which the expansion of the rock mass loose circle prevented effectively. The site test shows that the convergence rate of surrounding rock with the improved support was less than 0.2 mm/d, and the rock deformation of chamber and roadway suppressed significantly.